2005
DOI: 10.1080/01587910500291454
|View full text |Cite
|
Sign up to set email alerts
|

A Constructivist Model of Mentoring, Coaching, and Facilitating Online Discussions

Abstract: This case study of an online graduate course determines the message characteristics of the instructor, volunteer teaching assistants, and students in online discussions, and proposes a mentoring, coaching, and facilitating model for online discussions. The researchers developed a coding system based on the literature of mentoring, coaching, and facilitating to identify the characteristics of conference discussion messages. The instructor fostered the development of volunteer teaching assistants into coaches an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 27 publications
3
56
0
3
Order By: Relevance
“…One of the strongest themes in the cognitive competence domain for Collins et al (1989) and many other authors (Ryan et al 2000;Salmon 2004;Mash et al 2005;Murphy et al 2005;Hew & Knapczyk 2007) was maximising the personal potential Core-competence skills in e-mentoring of a mentee through achieving change by the medium of a reflective practice, resulting in changed perspectives and a reordering of priorities. Salmon (2002b) championed opportunities for reflection saying that they needed to be built into the design of every online conference and facilitated by a trained e-moderator.…”
Section: Online Cognitive Competence Domainmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the strongest themes in the cognitive competence domain for Collins et al (1989) and many other authors (Ryan et al 2000;Salmon 2004;Mash et al 2005;Murphy et al 2005;Hew & Knapczyk 2007) was maximising the personal potential Core-competence skills in e-mentoring of a mentee through achieving change by the medium of a reflective practice, resulting in changed perspectives and a reordering of priorities. Salmon (2002b) championed opportunities for reflection saying that they needed to be built into the design of every online conference and facilitated by a trained e-moderator.…”
Section: Online Cognitive Competence Domainmentioning
confidence: 99%
“…Reflecting Anderson et al's (2001) description of discourse facilitation, the discussion facilitators had to identify areas of agreement and disagreement; sought to reach consensus and understanding; encouraged, acknowledged or reinforced student contributions; set a climate for learning; drew in participants comments, prompting discussion; and assessed the efficacy of the process. They found that students became experts in the content that they facilitated (Murphy et al 2005) while learning to emulate the supervising instructor's facilitating approaches. Interestingly, they discovered that many students who had already been facilitators earlier in the semester adopted facilitating roles when they were participants in later discussions.…”
Section: Online Cognitive Competence Domainmentioning
confidence: 99%
See 3 more Smart Citations